ANALISIS KINERJA KEUANGAN DALAM PENGELOLAAN APBD PADA DINAS PENGELOLA KEUANGAN, PENDAPATAN DAN ASET (DPKPA) KABUPATEN MINAHASA SELATAN - Mandagi, Novita; Tinangon, Jantje J.; Warongan, Jessy D.L (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The ability of a region to carry out regional autonomy as measured by financial performance area. The size of the financial performance of one of them is financial management is reflected in the Regional Budget (APBD). This study aimed to analyze the financial performance in the management of budget revenues and expenditures at the Department of Financial Management, Revenue and Assets (DPKPA). In this study the methods of analysis used is descriptive analysis. Data analysis was performed by using financial ratio analysis area and the results are described / portrayed on how the analysis of the financial performance in the management of budget revenues and expenditures at the Department of Financial Management, Revenue and Assets of 2011-2014. The results showed that the ratio of independence included in the category of low, the ratio of the degree of decentralization included in the category of low, level of local financial activities included in the category of low, effective ratio shows the financial performance increased, and the level of efficiency is categorized still less efficient. South Minahasa District Government should optimize regional revenue collection and also perform priorities in budgetary spending in the area. Keywords : financial performance, budget revenue and expenditure, financial management